2017
DOI: 10.1080/19420889.2017.1338990
|View full text |Cite
|
Sign up to set email alerts
|

Keep it on the edge: The post-mitotic midbody as a polarity signal unit

Abstract: The maintenance of the epithelial architecture during tissue proliferation is achieved by apical positioning of the midbody after cell division. Consequently, midbody mislocalization contributes to epithelial architecture disruption, a fundamental event during epithelial tumorigenesis. Studies in 3D polarized epithelial MDCK or Caco2 cell models, where midbody misplacement leads to multiple ectopic but fully polarized lumen-containing cysts, revealed that this phenotype can be caused by 2 different scenarios: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…We show that internalization of post-mitotic MBs leads to an increase in proliferation in HeLa as well as MDA-MB-31 cell lines, supportive of the idea that post-abscission MB signaling is not just a Hela cell phenomenon but likely functions in other cell types as well. Consistently, recently published work from Lujan and colleagues demonstrated that post-abscission MBs can also regulate epithelial cell polarity in MDCK cells 41 . Based on all of these findings we propose that internalized MBs are long-lived signaling structures which affect several cellular structures and refer to them as MB-containing endosomes or MBsomes (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…We show that internalization of post-mitotic MBs leads to an increase in proliferation in HeLa as well as MDA-MB-31 cell lines, supportive of the idea that post-abscission MB signaling is not just a Hela cell phenomenon but likely functions in other cell types as well. Consistently, recently published work from Lujan and colleagues demonstrated that post-abscission MBs can also regulate epithelial cell polarity in MDCK cells 41 . Based on all of these findings we propose that internalized MBs are long-lived signaling structures which affect several cellular structures and refer to them as MB-containing endosomes or MBsomes (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…The mechanisms required for early local polarization of lateral puncta are unknown. Unlike in MDCK cysts, midbodies are unlikely to provide a polarizing cue since they are positioned on opposite membranes from lateral puncta (Bai et al, 2020; Li et al, 2014; Lujan et al, 2017). Instead, mitosis from E8 to E16 may promote formation of lateral puncta by trafficking polarity proteins along astral microtubules to their lateral attachment sites or by increasing the concavity of the cell membrane which can promote local accumulation of polarity proteins (Chiou et al, 2017; Feldman and Priess, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…3). Interestingly, this mechanism of cell-division linked lumenogenesis appears to be conserved in other specialized epithelial cell types, such as hepatocytes 24 and human intestinal cells 25 .…”
Section: Lumen Formation In Vitromentioning
confidence: 97%